ANALYSIS OF THE DEVELOPMENT OF THE NATIONAL SHIPMENT INDUSTRYIN SUPPORTING INDONESIA'S DEFENSE SECURITY TO MAINTAIN WATER SOVEREIGNTY IN INDONESIA'S TERRITORY - Antoni, Hendro; Feani, Dewi Puspaningtyas (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The formulation of defense technology is influenced by the philosophy and vision of the state as stated in Law No. 3 of 2002 concerning National Defense. Indonesia's vision in national defense and security requires independence in the field of national defense and security which is influenced by geographical conditions, the condition of defense and security equipment owned, and laws and regulations. The development of defense technology must be based on demographic aspects and geographical conditions that include the articulation of the archipelagic state (in accordance with the concept of the archipelagic outlook), and an archipelagic state (in accordance with UNCLOS 1982, the United Nations Convention on Law On the Seas).How is the relationship between the shipping industry and the shipping supporting industry? How is the concept of the national shipping industry to increase competitiveness in supporting Indonesia's maritime security? The research theory and concept use the Competitiveness Theory, Empowerm